The Role of Green Marketing Orientation and Brand Social Responsibility in Enhancing Consumers’ Intention to Purchase Environmentally Friendly Products - Risna Yulianti; Nina Fapari Arif (Institut Teknologi dan Bisnis Asia Malang, 2026)
The primary objective of this study is to investigate the impact of Green Marketing Orientation (GMO) on Green Purchase Intention (GPI) and to assess the mediating roles of Brand Social Responsibility (BSR) and Green Customer Loyalty (GCL) in shaping consumers’ intentions to purchase environmentally friendly products. The research involved 207 respondents aged 17 years and older who had previously purchased eco-friendly products. Participants were selected using a non-probability purposive sampling technique. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 3.0. These findings underscore the importance of not only adopting green marketing strategies but also consistently implementing them through effective social responsibility programs, thereby fostering loyal, environmentally conscious customers. However, this study acknowledges certain limitations, particularly its focus on a single industry sector, which restricts the generalizability of the results. Therefore, future research is recommended to expand the respondent scope across diverse sectors and utilize a longitudinal approach to gain a deeper and more comprehensive understanding of the long-term effects of green marketing orientation on consumer behavior.